Assessment of Vitamin D Deficiency, Consequences, and Treatment among Pregnant Women in Saudi Arabia: A Retrospective Cohort Study (Asian Journal of Pharmaceutics (AJP), 2025)
Vitamin D deficiency (VDD) during pregnancy is associated with adverse maternal and fetal outcomes.This study aimed to investigate the prevalence of VDD, its complications, and supplementation practices amongpregnant women in Riyadh, Saudi Arabia. Materials and Methods: A retrospective review of medical recordsfrom child-bearing women who attended prenatal clinics at King Khalid University Hospital in 2021 wasconducted. Data from 478 pregnant women were analyzed using the Statistical Package for the Social Sciencesversion 21. Descriptive and inferential statistics were applied, with P < 0.05 considered statistically significant.Results: The mean age of participants was 31.09 ± 5.71 years, and mean plasma Vitamin D (VD) level was34.26 ± 25.74 ng/mL. The prevalence of VD inadequacy was 55.4% (deficiency 27.5% and insufficiency 27.9%).Approximately 30% of women with VDD did not receive supplementation. Among supplemented women, most(n = 119, 67.2%) received cholecalciferol 50,000 IU weekly for 4 weeks. Predictors of VD plasma concentrationincluded maternal age (β = 1.049, P < 0.001), body weight (β = 0.275, P = 0.012), post-discharge hemoglobin(β = 2.193, P = 0.049), and neonatal pulse rate (β = −0.366, P = 0.021). The number of babies (odds ratio[OR] = 0.092, P = 0.003) and number of live births (OR = 0.416, P < 0.001) significantly predicted VDDprevalence. Common maternal complications included previous cesarean section (21.3%), gestational diabetesmellitus (14.6%), and hypothyroidism (7.3%). Conclusion: VDD is highly prevalent among pregnant womenin Riyadh, and supplementation practices often do not follow recommended guidelines. Educational campaignstargeting both pregnant women and healthcare providers are needed to improve awareness, prevent VDD-relatedcomplications, and promote safe, guideline-based VD supplementation during pregnancy.